Improving Students’ Vocabulary Ability Through Crossword Puzzle At Grade VIII Of MTS N 2 Konawe - Iin Wahyudi (Universitas Pahlawan Tuanku Tambusai, 2023)
This research aimed to know whether crossword puzzle can improve student vocabulary ability the research methodology used in this research was classroom action research. The place of this research was at second grade of MTs N 2 Konawe. The subject of this research was class B which consists of 28 students. To find the improvement of students' vocabulary ability, the researcher used multiple choice tests. There were two cycles; each cycle consisted of two meetings and each meeting consisted of planning, action, observation, and reflection. The researcher found that the students involved actively in teaching learning processes, they more encouraged and were enjoyed in studying English than before. The result of students vocabulary test on pre test 9 students or 36% who got score above the Minimum Mastery Criterion meanwhile the other 19 students were below criterion, the first cycle 16 students or 64 % who got score above the Minimum Mastery Criterion meanwhile the other 11 students were below criterion. Then, on second cycle there are 22 students or 80 % who got score above the Minimum Mastery Criterion meanwhile the other 3 students were below criterion. So the result of students’ achievement increases (16%) between cycle 1 and cycle 2. The last meeting crosswords puzzle applied teaching vocabulary ability of classification words as bellow: verb, noun, adverb and adjective could be effective improved vocabulary ability. Base on the result of the study concluded learning trough crossword puzzle suitable improve vocabulary ability students’.